Memórias sobre a infância no meio rural: a escola e os outros espaços de sociabilidade (Minas Gerais - Brasil, 1920-1950) - Mônica Y. Jinzenji; Ana M. Galvão; Simone A. Silva (Universidade do Minho, 2012)
This paper analyses the representations of childhood by women of rural communities from the state of Minas Gerais, in the first half of the 20th century, who have migrated to Belo Horizonte as adults and live in a suburban area of the Minas Gerais capital. We interviewed 13 women, and gathered demographic data and educational legislation of that period. During the interviews, the recurrent statement "I had no childhood" can be understood as a contraposition made by them between a supposed ideal childhood, related to socially privileged classes, and childhood nowadays, the one they were excluded from. The evoked memories refer to the intense work routine in the field and in other people's houses, the hardships to frequent a school, the poor state of the clothes, the lack of toys, but also the joyful moments of games and the participation on religious celebrations. Family, work and religion compete with the school as important spaces of sociability.